Evaluation of Babinski reflex in term neonates with hypoxic ischemic encephalopathy: a cross sectional observational study - Chikkanna, Somashekhar; V., Nagaraj M.; R., Bhavana K.; N., Shwetha (International Journal of Contemporary Pediatrics, 2020)
Background: Assessment of primitive reflexes is one of the earliest, easiest and most frequently used method among health care workers for newborns and young infants. Babinski reflex is one of the infantile reflexes. Our aim was to study Babinski reflex in a term neonates with hypoxic ischemic encephalopathy (HIE). Methods: This study is a cross-sectional observational study. 100 consecutive neonates fulfilling criteria of HIE according to Sarnat and Sarnat classification, admitted in our neonatal intensive care unit (NICU) were included. It was elicited from 12 hours after birth to 72 hours of birth. Babinski response was assessed using thumb nail drag method. Results: 78% babies are term babies. 22% babies are post term babies. Male to female ratio is 1.5:1. 38% neonates belong to HIE stage I, 39% and 33% neonates belong to HIE stage II and III respectively. In HIE stage I, planter grasp was elicitable in 89%. It remain non-elicitable in 44% and 91% in HIE stages II and III respectively. Conclusions: Absence of Babinski reflex can be correlated with the increase in severity of HIE. It is important to include the assessment of Babinski reflex along with other primitive reflexes in the newborn generally and especially in HIE.